Old-new disease is maize smut (Ustilago maydis) - Frommer, Dóra; Veres, Szilvia; Lévai, László; Radócz, László (Acta Agraria Debreceniensis, 2015)
Corn smut disease (Ustilago maydis) is one of the most common maize diseases. In the previous years the disease lost some from its importance, however nowadays it turns into more and more important and widespread one. The control encounters great difficulties, therefore it should be emphasized the preventive and resistance-based protection.